Capturing climate change. - Perry, T.S (IEEE spectrum)
Though for decades arguments have raged over whether human activities cause changes in climate, these battles may be nearing an end. It is hard to dispute that the earths climate is getting warmer. The apparent reason is a measurable increase in greenhouse gases, most notably carbon dioxide, but also methane, nitrous oxide, chlorofluorocarbons (CFCs), and ozone. Some do disagree. And this group, while not large, is vocal. Some accept the evidence for a warming planet, but not that it is due to human activities. Others think a negative feedback effect will kick in or that the effects will be minor or even positive. But many scientists say global warming is real and will have serious effects. They also believe that nothing we do now can immediately stop it. Our best efforts, though important, will only slow it down. The questions of today are how well the effects can be predicted and how to cope with them. This paper discusses the evidence for global warming and climate models to test the theory. The possible effects of global warming are described. The political action being taken regarding global warming are discussed